AN ANALISYS OF STUDENT’S PRONOUNCIATION ERROR MADE IN SPEAKING CLASS AT ENGLISH CLUB LUBANGSA PUTRI ANNUQAYAH GULUK-GULUK SUMENEP - Arjaniyanti, Arjaniyanti; Anjarani, Devie Reztia (Universitas Madura, 2025)
The objective of this research is to find out the kinds of errors in pronunciation and the sources of errors in pronunciation at basic class of At English Club Lubangsa Putri Annuqayah Guluk-Guluk Sumenep. This research is expected as guidance for the teacher to know about the students’ errors in using English in conversation. So the teacher can formulate some methods or strategies in teaching English pronunciation.The method of this research is the qualitative in order to interpret the data of the research. The population of this research was the basic class of At English Club Lubangsa Putri Annuqayah Guluk-Guluk Sumenep. The writer chose the basic class as sample by using total sampling technique because of the population was less than one hundred students and the sample consists of 18 students. A test was applied as instrument in this research which is consisted of some words to be pronounced. The writer interprete the data descriptively and the result shows that The Students of the basic class of At English Club Lubangsa Putri Annuqayah Guluk-Guluk, The misformission error amount 67, 53%, its get from 16 words and 112 students who are made pronounciation error. The addition error amount 24, 7%, its get from 6 words and 45 students who are made pronounciation error. The omission error amount 13,7%, its get from4 words and 25 students who are made pronounciation error by analyzing the source the writer found that there are two sources of errors that students had; firstly, they were pronouncing English word as written and overgeneralization when they were pronouncing the word.